Septic Pulmonary Embolism Following Appendectomy Surgery - Soroy Lardo; Anna Ariane; Khie Chen (Interna Publishing, 2015)
Septic Pulmonary embolism is a rare condition where there were numerous pulmonary infarcts resulting from blood clot emboli that also contains microorganism. This disorder is insidious onset, Its clinical features usually unspecific and the diagnosis usually difficult to establish. A 43 old woman who underwent an appendicitis surgery, reentered the hospital at the sixth day after surgery presented with fever, pain at the surgical site, progressive severe dyspnea and chest tightness. From the physical examination finding there were tachycardia, tachypneu, wet rough basal rhonki on the right rear and tenderness at right lower region of the abdomen. The thorax-abdomen CT scan result was pleuropneumonial with minimal effusion in the right side. ACT angiography scan of the chest and abdomen showed intralumen emboli in medial lobe segmen of right pulmonary artery, right pleuropneumonia with segmental lession in segmen 10 right lobe and inflammation process along right lateral wall of the abdomen. Laboratory results that also supported diagnosis were D dimer 3442 ng/mL and culture result from surgical site pus showed E. Coli ESBL (+). Base on these findings, this case was established as a septic pulmonary embolism. Key words: septic pulmonary embolism, appendicitis surgery, E. coli ESBL (+).